Microsoft Azure for dummies - Warner, Timothy L. (John Wiley & Sons, Incorporated, 2020)
Intro -- Table of Contents -- Introduction -- About This Book -- Foolish Assumptions -- Icons Used in This Book -- Beyond the Book -- Where to Go from Here -- Part 1: Getting Started with Microsoft Azure -- Chapter 1: Introducing Microsoft Azure -- What Is Cloud Computing? -- Understanding Cloud Computing Models -- Introducing Microsoft Azure Services -- Starting Your First Azure Subscription -- Chapter 2: Exploring Azure Resource Manager -- Introducing Azure Resource Manager -- Getting Familiar with Azure Regions -- Introducing the Azure Management Tools -- Part 2: Deploying Compute Resources to Microsoft Azure -- Chapter 3: Managing Storage in Azure -- Understanding Azure Storage Data Types -- Working with a Storage Account -- Introducing Azure Disk Storage -- Chapter 4: Planning Your Virtual Network Topology -- Understanding Virtual Network Components -- Creating a Virtual Network -- Configuring Virtual Networks -- Connecting Virtual Networks -- Chapter 5: Deploying and Configuring Azure Virtual Machines -- Planning Your VM Deployment -- Recognizing Azure VM Components -- Architectural Considerations -- Deploying Azure VMs from the Azure Marketplace -- Configuring Your VMs -- Starting, Stopping, and Resizing VMs -- Chapter 6: Shipping Docker Containers in Azure -- Understanding Docker -- Implementing Azure Container Instances -- Storing Images in Azure Container Registry -- Introducing Azure Kubernetes Service -- Using Containers with Azure App Service -- Part 3: Deploying Platform Resources to Microsoft Azure -- Chapter 7: Deploying and Configuring Azure App Service Apps -- Introducing Azure App Service -- Deploying Your First Web App -- Configuring a Web App -- Monitoring a Web App -- Chapter 8: Running Serverless Apps in Azure -- Defining Serverless -- Working with Azure Functions -- Building Workflows with Azure Logic Apps
Auf dem Cover: "Uncover the shortcuts for migrating to Azure; deploy web applications that scale to your needs; apply the latest security to keep your data private"
Keywords: Electronic books